Efek Paparan Radiasi Gamma dan Pemberian Ekstrak Temulawak (Curcuma xanthorrhiza) Terhadap Pelebaran Vena Centralis Hepar Mencit (Mus musculus) - Septiana Kurnia Sari; C S Widodo; U P Juswono (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2018)
Gamma radiation is ionizing radiation causes cells damage. It was caused by interaction of radiation with cells can produce free radical. The cell defense mechanisms againts free radical involves an antioxidant that can neutralize and catch it. The objectives of this research were to analyze effects of gamma radiation exposure and treated with Curcuma xanthorrhiza extract in central vein to the mice’s liver. Eighty mices were used in this research and divided into three groups, negative control (K-), radiation non extract (R-) and extract plus radiation (R+). The mice were treated with 1.4; 2.0; 2.6; 3.2 and 3.8 gr/kg body weight. The exposure of gamma radiation are given during 10, 20, 30, 40 and 50 minutes. The measuring of central vein area is done by observated microscopic picture mice’s liver. The results showed that free radical forms lipid peroxidation that causes necrosis to the liver cells, one of them is widening of central vein. The treatment with Curcuma xanthorrhiza extract can prevent the enlargement of central vein with increasing Curcuma xanthorrhiza extract dosage, from 129424 µm2 menjadi 12941 µm2. Curcuma xanthorrhiza extract contains curcumin that can inhibit forming free radical because of gamma radiation to liver.